Axillary artery loop interposition graft (AALG) as unusual access for hemodialysis - Fareed, Abdelmieniem; Zaid, Nehad; Alkhateep, Yahia M. (International Surgery Journal, 2017)
Background: Life expectancy of end stage renal disease patients continues to lengthen and with the limited durability of vascular accesses, repeat fistula construction at different levels of the upper limb is often necessary and leads ultimately to exhaustion of autogenous vascular access sites. Our experience with alternative vascular access procedures namely the arterio-arterial loop graft in the first part of axillary artery was presented in this study. Methods: From June 2013 to Aug 2017, arterio-arterial interposition loop graft procedures (AALG) for vascular access were performed in 15 patients with end-stage renal disease. Inclusion criteria were patients with unsuitable large deep veins or with cardiac insufficiency intolerable to high-flow arterio-venous fistula. Results: The achieved primary and secondary patency was 73.3 % and 86.6% at 1 year and 53.3 % and 66.7 % at 3 years. Severe infection in whole graft occurred in two patients (13.3%) after 11, 27 months. One patient died six months after operation due to unrelated cause. two patients had pseudoaneurysms after 20 and 28 months at sites of repetitive needle puncture and were treated successfully by segmental replacement. Conclusions: In selected cases and with proper indication the AALG can offer efficient alternative for vascular hemodialysis access and can improve the survival rate of such patients.